Literacki opór wobec lektury odczarowującej - Ostrowski, Marek (Przestrzenie Teorii, 2019)
The paper deals with issues regarding the disenchantment of literature stemming from the instrumental approach in literary studies. It highlights cases of resistance to this disenchantment of literature both in academic and literary works. The instrumental lecture is contrasted with the creative one, which results from opening up to otherness contained within the text. The creation of unassimilated otherness is the drving force of the literary avant-garde, which uses it as a defence against scientific disenchantment. Possible reasons for the feeling of literary disenchantment are discussed in this paper and the validity of such fears is taken into consideration.